Modified magnesium hydride composite material, method for preparing the same and use thereof
Patent Information
- Application Number
- CN202510901465.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-01
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-07-01
AI Technical Summary
镁基储氢材料的动力学性能较为缓慢,中低温脱氢速率远不能满足实际应用需求。
The NiTi-LMO composite catalyst was combined with MgH2. The NiTi-LDH precursor was prepared and calcined under a protective atmosphere to form the NiTi-LMO composite catalyst. Surfactants were added to improve the catalytic effect. The catalyst formed multi-metal element doping or heterojunction, providing more active sites and promoting hydrogen molecule dissociation and Mg-H bond breaking.
It significantly improves the hydrogen absorption and desorption rate and stability of magnesium-based hydrogen storage materials, and the hydrogen storage capacity remains above 95% after 50 cycles, making it suitable for large-scale production.
Smart Images

Figure CN120681720B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrogen storage materials technology, and relates to a modified magnesium hydride composite material, its preparation method and application. Background Technology
[0002] Hydrogen energy boasts numerous advantages, including abundant resources, cleanliness, and high efficiency, making it a crucial component of my country's energy structure. However, safe and efficient hydrogen storage and transportation technologies are a key technological bottleneck hindering the industrialization of hydrogen energy. Magnesium-based hydrogen storage materials possess the highest theoretical hydrogen storage capacity among metallic hydrogen storage materials, with a theoretical hydrogen storage capacity of 7.6 wt.% and a volumetric hydrogen storage density of 110 g / L. Furthermore, they are inexpensive, abundant, and exhibit stable hydrogen absorption and desorption cycle characteristics, making them one of the most promising hydrogen storage materials currently available.
[0003] Compared to traditional high-pressure gas cylinders, hydrogen storage tanks using magnesium-based hydrogen storage materials have higher hydrogen density, can reduce volume by at least two-thirds, and can be further reduced in weight. This enables large-capacity, long-distance, low-cost, and highly safe hydrogen transportation, offering numerous advantages in the future hydrogen energy industry that high-pressure gaseous hydrogen and liquid hydrogen cannot match, and thus has broad market prospects. However, to meet practical application requirements, magnesium-based hydrogen storage materials still suffer from relatively slow kinetic performance, and their low-to-medium temperature dehydrogenation rates are far from meeting the demands of real-world applications. Summary of the Invention
[0004] To address the above problems, this invention provides a modified magnesium hydride composite material, as well as a method for preparing the modified magnesium hydride composite material and its applications.
[0005] The technical solution is as follows:
[0006] A modified magnesium hydride composite material comprising a NiTi-LMO composite catalyst and MgH2, wherein LMO represents a layered metal oxide.
[0007] In some embodiments, the NiTi-LMO composite catalyst further includes a surfactant.
[0008] In some embodiments, the surfactant includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium fatty alcohol ether sulfate.
[0009] In some embodiments, the molar ratio of the surfactant to the Ti is less than 1:1.
[0010] In some embodiments, the molar ratio of Ni to Ti in the NiTi-LMO composite catalyst is (3-4):1.
[0011] In some embodiments, the composite material comprises, by weight percentage, 3 wt.% to 9 wt.% of the NiTi-LMO composite catalyst and 91 wt.% to 97 wt.% of the MgH2.
[0012] In some embodiments, the NiTi-LMO composite catalyst is a NiO-TiO2 layered metal oxide and / or a Ni-TiO2 layered metal oxide.
[0013] The present invention also provides a method for preparing the above-mentioned modified magnesium hydride composite material, comprising the following steps:
[0014] NiTi-LDH precursor was prepared by mixing nickel source, titanium source and precipitant and reacting them under heat.
[0015] The NiTi-LDH precursor was calcined under a protective atmosphere to prepare a NiTi-LMO composite catalyst.
[0016] The NiTi-LMO composite catalyst was mixed with MgH2 to prepare the composite material.
[0017] In some embodiments, a surfactant is also added during the preparation of the NiTi-LDH precursor.
[0018] In some embodiments, the molar ratio of the surfactant to the titanium source is less than 1:1.
[0019] In some embodiments, the surfactant includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium fatty alcohol ether sulfate.
[0020] In some embodiments, the molar ratio of the nickel source to the titanium source is (3-4):1.
[0021] In some embodiments, the molar ratio of the titanium source to the precipitant is 1:(50-100).
[0022] In some embodiments, the nickel source includes one or more of nickel chloride, nickel nitrate, and nickel carbonate.
[0023] In some embodiments, the titanium source includes one or more of isopropyl titanate, tetrabutyl titanate, titanium tetrachloride, and titanium tetraisopropoxide.
[0024] In some embodiments, the precipitant includes urea.
[0025] In some embodiments, the solvent includes water.
[0026] The present invention also provides a hydrogen storage material, wherein the hydrogen storage material comprises the modified magnesium hydride composite material described above or the modified magnesium hydride composite material prepared by the above preparation method.
[0027] The present invention has the following beneficial effects:
[0028] This invention provides a modified magnesium hydride composite material, comprising a NiTi-LMO composite catalyst and a MgH2 composite material. The composite catalyst of this invention comprises a Ni and Ti bimetallic compound, thereby enabling the NiTi-LMO composite catalyst of this invention to form a multi-metal element doped or heterojunction, exhibiting excellent catalytic effect on MgH2. The heterostructure of the catalyst can also provide more active sites. When the above composite catalyst is applied to MgH2 hydrogen storage materials, the catalyst can accelerate the dissociation of hydrogen molecules, promote the breaking of Mg-H bonds, provide more active sites, and provide channels for the diffusion of hydrogen atoms, thereby improving the hydrogen storage performance of MgH2.
[0029] The preparation process of this invention is simple, the raw materials are readily available, and it is suitable for large-scale production.
[0030] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description
[0031] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein:
[0032] Figure 1 The image shows a comparison of the XRD patterns of the NiTi-LDH-0.5SDS precursor prepared in Example 1 and the NiTi-LDH prepared in Example 3.
[0033] Figure 2 The XRD pattern of the NiO-TiO2-0.5SDS catalyst prepared in Example 1 is shown.
[0034] Figure 3 The image shows a SEM image of the NiO-TiO2-0.5SDS catalyst prepared in Example 1.
[0035] Figure 4 SEM images and particle size distribution diagrams of the MgH2-6%NiO-TiO2-0.5SDS composite hydrogen storage material prepared in Example 1 are shown.
[0036] Figure 5The image shows the XRD pattern of the Ni-TiO2-0.5SDS catalyst prepared in Example 2.
[0037] Figure 6 The image shows a SEM image of the Ni-TiO2-0.5SDS catalyst prepared in Example 2.
[0038] Figure 7 SEM images and particle size distribution diagrams of the MgH2-6%Ni-TiO2-0.5SDS composite hydrogen storage material prepared in Example 2 are shown.
[0039] Figure 8 The image shows a comparison of the XRD patterns and SEM images of the NiTi-LDH-0.5SDS precursor prepared in Example 1 and the NiTi-LDH-xSDS precursors (x = 0.25, 0.75, 1) prepared in Examples 5-7.
[0040] Figure 9 The image shows a comparison of the XRD patterns and SEM images of the NiO-TiO2-0.5SDS catalyst prepared in Example 1 with the NiO-TiO2-0.5SDS-T (T = 400, 500, 550) prepared in Examples 11-13.
[0041] Figure 10 The temperature-dependent hydrogen desorption (TPD) curves of ball-milled pure MgH2 powder (Comparative Example 1), MgH2-6 NiO-TiO2-0.5SDS prepared in Example 1, and MgH2-6 Ni-TiO2-0.5SDS composite hydrogen storage materials prepared in Example 2 are shown.
[0042] Figure 11 Isothermal hydrogen desorption curves of ball-milled pure MgH2 powder in Comparative Example 1 and the MgH2-6 NiO-TiO2-0.5SDS composite hydrogen storage material prepared in Example 1;
[0043] Figure 12 Isothermal hydrogen absorption curves of ball-milled pure MgH2 powder in Comparative Example 1 and the MgH2-6 NiO-TiO2-0.5SDS composite hydrogen storage material prepared in Example 1;
[0044] Figure 13 The graph shows the hydrogen absorption and desorption performance of the MgH2-6 NiO-TiO2-0.5SDS composite hydrogen storage material prepared in Example 1 at 300℃.
[0045] Figure 14 Isothermal hydrogen desorption curves of ball-milled pure MgH2 powder in Comparative Example 1 and the MgH2-6%Ni-TiO2-0.5SDS composite hydrogen storage material prepared in Example 2;
[0046] Figure 15 Isothermal hydrogen absorption curves of ball-milled pure MgH2 powder in Comparative Example 1 and the MgH2-6%Ni-TiO2-0.5SDS composite hydrogen storage material prepared in Example 2;
[0047] Figure 16 The graph shows the hydrogen absorption and desorption performance of the MgH2-6%Ni-TiO2-0.5SDS composite hydrogen storage material prepared in Example 2 at 300℃.
[0048] Figure 17 The hydrogen desorption curves (TPD curves) of the MgH2-6%NiO-TiO2 composite hydrogen storage materials prepared in Example 3 and Example 4 are shown.
[0049] Figure 18 The isothermal hydrogen desorption curve of the MgH2-6 NiO-TiO2 composite hydrogen storage material prepared in Example 3 is shown below.
[0050] Figure 19 The isothermal hydrogen desorption curve of the MgH2-6 Ni-TiO2 composite hydrogen storage material prepared in Example 4 is shown. Detailed Implementation
[0051] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. Unless otherwise specified, the following embodiments and features can be combined with each other.
[0052] The accompanying drawings are for illustrative purposes only and are schematic diagrams, not actual pictures. They should not be construed as limiting the invention. To better illustrate the embodiments of the invention, some parts in the drawings may be omitted, enlarged, or reduced, and do not represent the actual product dimensions. It is understandable to those skilled in the art that some well-known structures and their descriptions may be omitted in the drawings.
[0053] In the accompanying drawings of the embodiments of the present invention, the same or similar reference numerals correspond to the same or similar components. In the description of the present invention, it should be understood that if terms such as "upper," "lower," "left," "right," "front," and "rear" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, they are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the terms used to describe positional relationships in the drawings are only for illustrative purposes and should not be construed as limiting the present invention. For those skilled in the art, the specific meaning of the above terms can be understood according to the specific circumstances.
[0054] In this invention, LDH represents layered double hydroxides, a type of layered material with a two-dimensional nanostructure, also known as hydrotalcite, hydrotalcite-like material, or anionic clay. LMO represents layered metal oxide, specifically a derivative obtained by calcining layered double hydroxide (LDH) as a precursor.
[0055] To address the problems of high dehydrogenation temperature, slow kinetic performance, and low-temperature dehydrogenation rate in current magnesium-based hydrogen storage materials that cannot meet the needs of practical applications, this invention provides a modified magnesium hydride composite material. The composite material includes a NiTi-LMO composite catalyst and MgH2, wherein LMO represents a layered metal oxide.
[0056] Based on the advantages of multi-metal components, the composite catalyst of this invention can form related metal element doping or heterojunctions, which have a good catalytic effect on MgH2. The heterostructure of the catalyst can also provide more active sites. When the above composite catalyst is applied to MgH2 hydrogen storage materials, the catalyst can accelerate the dissociation of hydrogen molecules, promote the breaking of Mg-H bonds, provide more active sites, and provide channels for the diffusion of hydrogen atoms, thereby improving the hydrogen storage performance of MgH2.
[0057] In some of these examples, the NiTi-LMO composite catalyst has an ultrathin / hollow structure.
[0058] The morphology and particle size of catalyst materials are important factors affecting catalytic reactions. Different morphologies and sizes lead to changes in the specific surface area, active site distribution, and surface electronic structure of the catalyst, thereby affecting catalytic activity and product selectivity. Generally, ultrathin and hollow structures, as well as reduced particle size, usually increase the specific surface area of the catalyst, thus providing more active sites.
[0059] In some examples, the NiTi-LMO composite catalyst further includes a surfactant. In some specific examples, the surfactant includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium fatty alcohol ether sulfate.
[0060] In some specific examples, the molar ratio of the surfactant to the Ti is less than 1:1; preferably, the molar ratio of the surfactant to the Ti is (0.25 to 0.75):1.
[0061] In some of these examples, the molar ratio of Ni to Ti in the NiTi-LMO composite catalyst is (3-4):1.
[0062] In some of these examples, the composite material comprises, by mass percentage, 3 wt.% to 9 wt.% of the NiTi-LMO composite catalyst and 91 wt.% to 97 wt.% of the MgH2.
[0063] In some examples, the NiTi-LMO composite catalyst is a NiO-TiO2 layered metal oxide and / or a Ni-TiO2 layered metal oxide.
[0064] The present invention also provides a method for preparing the above-mentioned modified magnesium hydride composite material, comprising the following steps:
[0065] S100: NiTi-LDH precursor is prepared by mixing nickel source, titanium source and precipitant and reacting by heating.
[0066] This invention prepares a nanosheet-like NiTi-LDH precursor via a step S100. This precursor exhibits a unique morphology of upright, interlaced thin sheets. When used as a support, the large specific surface area of the NiTi-LDH precursor provides more active sites for the metal, resulting in more uniform metal dispersion. This method achieves both support synthesis and loading in a single reaction, demonstrating a simple preparation process.
[0067] In some specific examples, the nickel source includes one or more of nickel chloride, nickel nitrate, and nickel carbonate.
[0068] In some specific examples, the titanium source includes one or more of isopropyl titanate, tetrabutyl titanate, titanium tetrachloride, and titanium tetraisopropoxide.
[0069] In some specific examples, the precipitant includes urea.
[0070] In some specific examples, the solvent includes water.
[0071] In some specific examples, the molar ratio of the nickel source to the titanium source is (3-4):1.
[0072] In some specific examples, the molar ratio of the titanium source to the precipitant is 1:(50-100).
[0073] In some preferred examples, a surfactant is also added during the step of preparing the NiTi-LDH precursor. Understandably, by adding a surfactant during the step of preparing the NiTi-LDH precursor, the precursor prepared by step S100 is a NiTi-LDH-surfactant precursor.
[0074] In some specific examples, the surfactant includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium fatty alcohol ether sulfate.
[0075] In some specific examples, the molar ratio of the surfactant to the titanium source is less than 1:1; preferably, the molar ratio of the surfactant to the titanium source is (0.25 to 0.75):1.
[0076] In some specific examples, the heating reaction is carried out in a water bath or an oil bath; more specifically, the heating reaction is carried out under stirring conditions at a stirring speed of 800 rpm to 1000 rpm.
[0077] In some specific examples, the temperature of the heating reaction is 80°C to 90°C.
[0078] In some specific examples, the heating reaction time is 24h to 27h.
[0079] In some specific examples, the heating reaction is followed by washing and a first filtration step. More specifically, washing involves repeated centrifugation with deionized water and undiluted ethanol until the solution pH is neutral, at a speed of 3000 rpm to 6000 rpm. The first filtration involves filtering the washed mixture and collecting the first filter residue.
[0080] In some specific examples, a purification step is also included; purification includes ultrasonic exfoliation, centrifugation, obtaining a second filter residue through a second filtration, and freeze-drying the second filter residue. In some more specific examples, ultrasonic exfoliation involves mixing the first filter residue with anhydrous ethanol and ultrasonicating at room temperature for 6 to 18 hours. In some more specific examples, the drying step employs freeze-drying.
[0081] S200: The NiTi-LDH precursor is calcined under a protective atmosphere to prepare a NiTi-LMO composite catalyst. In some specific examples, the protective atmosphere is argon, and the NiTi-LMO composite catalyst is a NiO-TiO2 layered metal oxide.
[0082] In some specific examples, the protective atmosphere is an argon-hydrogen mixture, and the NiTi-LMO composite catalyst is a Ni-TiO2 layered metal oxide; more specifically, the volume ratio of argon to hydrogen in the argon-hydrogen mixture is 95:5.
[0083] In some preferred examples, when the precursor of NiTi-LDH-surfactant is prepared in step S100, the composite catalyst prepared by calcination in step S200 under a protective atmosphere is NiTi-LMO-surfactant; specifically, when the protective atmosphere is argon, the NiTi-LMO-surfactant is NiO-TiO2-surfactant, including but not limited to NiO-TiO2-SDS; when the protective atmosphere is an argon-hydrogen mixture, the NiTi-LMO composite catalyst is Ni-TiO2-surfactant, including but not limited to NiO-TiO2-SDS.
[0084] This invention significantly improves the structural stability of layered double hydroxide (LDH) materials during high-temperature calcination by doping the precursor with a surfactant. The interaction strength between the surfactant and the LDH host layers is significantly better than that of traditional intercalated anions (such as CO32-). 2- Its essence stems from the hydrogen bond coordination effect formed between surfactant molecules and the metal sites of LDH layers. This coordination can generate strong electronic interactions, which significantly improves the binding energy compared to traditional anionic intercalation systems. This synergistic stabilization mechanism can effectively suppress the collapse of the interlayer structure under high temperature conditions and help the calcined product maintain the nanosheet structure of the precursor.
[0085] In some specific examples, the calcination temperature is 450℃~480℃;
[0086] In some specific examples, the calcination time is 2h to 3h.
[0087] The NiTi-LDH precursor prepared by the S100 step, possessing a unique morphology, can be calcined under different conditions to prepare a NiTi-LMO catalyst that maintains the ultrathin / hollow structure of the LDH precursor. The uniform distribution of the two metal atoms in the LDH inhibits further growth and aggregation of NiO, Ni, and TiO2 during heat treatment. Furthermore, it fully utilizes the multi-metal composition advantage of the LDH precursor to form related metal element doping or heterojunctions. Heterogeneous structures can provide more active sites. Therefore, the catalyst material of this invention not only possesses abundant reactive active sites but can also further improve the hydrogen storage performance of MgH2 through synergistic catalysis via doping / heterogeneous junction formation.
[0088] S300: The composite material is prepared by mixing the NiTi-LMO composite catalyst and MgH2.
[0089] In some specific examples, the NiTi-LMO composite catalyst and the MgH2 are mixed using mechanical ball milling.
[0090] In some specific examples, the mechanical ball milling method uses stainless steel balls as grinding beads and argon gas as the grinding atmosphere.
[0091] In some specific examples, the ball-to-material ratio of the ball milling method is 20–40:1, and the ball milling is performed intermittently in both forward and reverse directions at a speed of 200 rpm–800 rpm for 10–20 hours. More specifically, the intermittent ball milling in both forward and reverse directions is defined as follows: after each ball milling session of 5–20 minutes, a pause of 5–20 minutes is performed.
[0092] The present invention also provides a hydrogen storage material, wherein the hydrogen storage material comprises the above-mentioned modified magnesium hydride composite material.
[0093] This invention prepares a composite material by mixing NiTi-LMO composite catalyst with magnesium hydride. When applied to the field of hydrogen storage materials, it exhibits excellent catalytic effects, not only improving the hydrogen absorption and desorption rate and the amount of hydrogen absorbed and desorbed, but also demonstrating stable hydrogen storage cycle kinetics. After 50 hydrogen absorption and desorption cycles, the hydrogen storage capacity can still be maintained at over 95%.
[0094] This invention designs a simple, inexpensive, and efficient magnesium-based hydrogen storage material system, providing ideas and methods for the design and large-scale commercial application of magnesium-based hydrogen storage materials.
[0095] The following are specific embodiments. Unless otherwise specified, the instruments, reagents, and materials involved in these embodiments are all conventional instruments, reagents, and materials already existing in the prior art and can be obtained through legitimate commercial channels. Unless otherwise specified, the experimental methods and detection methods involved in the following embodiments are all conventional experimental methods and detection methods already existing in the prior art.
[0096] Example 1
[0097] (1) Preparation of NiTi-LDH-0.5SDS precursor
[0098] At room temperature, 4 mmol of nickel chloride hexahydrate (NiCl2·6H2O) and 1 mmol of isopropyl titanate (C 12 H 28O4Ti), 0.05 mol urea (CH4N2O), and 0.5 mmol sodium dodecyl sulfate (SDS) were dissolved in 50 mL of deionized water and magnetically stirred until homogeneous. The homogeneous solution was then placed in a constant-temperature water bath and reacted at 90 °C with stirring for 24 h. After the reaction, the resulting mixture was washed with deionized water and then with anhydrous ethanol at 6000 rpm until the pH of the supernatant was neutral. The supernatant was then filtered to obtain a green powder product. This green powder product was placed in 50 mL of anhydrous ethanol and ultrasonically exfoliated at room temperature for 6 h. The resulting suspension was then centrifuged at 6000 rpm and filtered to obtain a moist green solid powder. Further freeze-drying yielded NiTi-LDH-0.5SDS precursor powder.
[0099] (2) Preparation of NiTi-LMO-0.5SDS composite catalyst
[0100] The NiTi-LDH-0.05SDS precursor obtained in step (1) was calcined under pure argon conditions at a calcination temperature of 450℃ for 2 hours to obtain the composite catalyst, named NiO-TiO2-0.5SDS.
[0101] (3) Preparation of MgH2-6%NiO-TiO2-0.5SDS composite hydrogen storage material
[0102] 0.06g of the NiO-TiO2-0.5SDS catalyst powder prepared above was mixed with 0.94g of pure MgH2 powder under a high-purity argon atmosphere, and then subjected to high-energy mechanical ball milling for 20h under an argon atmosphere to prepare MgH2-6%NiO-TiO2-0.5SDS composite hydrogen storage material. During the ball milling process, the ball-to-material ratio was 20:1, the ball milling speed was 400rpm, the ball milling jar was a 100mL stainless steel jar, and the ball milling beads were 5mm and 10mm in diameter stainless steel. An intermittent ball milling method was adopted, i.e., rotating forward at 400rpm for 10min, then resting for 10min, then rotating in reverse for 10min, then resting for 10min, for a total effective ball milling time of 10h.
[0103] Example 2
[0104] (1) Preparation of NiTi-LDH-0.5SDS precursor
[0105] Similar to Example 1, a NiTi-LDH-0.5SDS precursor was prepared;
[0106] (2) Preparation of NiTi-LMO-0.5SDS composite catalyst
[0107] The process was basically the same as in Example 1, except that the calcination atmosphere was argon-hydrogen (argon to hydrogen volume ratio 95:5), and Ni-TiO2-0.5SDS was prepared.
[0108] (3) Preparation of MgH2-6%Ni-TiO2-0.5SDS composite hydrogen storage material
[0109] Similar to Example 1, a MgH2-6%Ni-TiO2-0.5SDS composite hydrogen storage material was prepared.
[0110] Example 3
[0111] (1) Preparation of NiTi-LDH precursor
[0112] This step is basically the same as in Example 1, except that sodium dodecyl sulfate (SDS) is not doped to obtain the NiTi-LDH precursor;
[0113] (2) Preparation of NiTi-LMO composite catalyst
[0114] Similar to Example 1, a NiO-TiO2 composite catalyst was prepared.
[0115] (3) Preparation of composite hydrogen storage materials
[0116] Similar to Example 1, a MgH2-6%NiO-TiO2 composite hydrogen storage material was prepared.
[0117] Example 4
[0118] (1) Preparation of NiTi-LDH precursor
[0119] This step is basically the same as in Example 2, except that sodium dodecyl sulfate (SDS) is not doped to obtain the NiTi-LDH precursor;
[0120] (2) Preparation of NiTi-LMO composite catalyst
[0121] The steps are basically the same as in Example 2 to prepare the Ni-TiO2 catalyst.
[0122] (3) Preparation of MgH2-6%Ni-TiO2 composite hydrogen storage material
[0123] Similar to Example 2, a MgH2-6%Ni-TiO2 composite hydrogen storage material was prepared.
[0124] Example 5
[0125] (1) Preparation of NiTi-LDH-0.25SDS precursor
[0126] This step is basically the same as in Example 1, except that the doping amount of sodium dodecyl sulfate (SDS) is changed to 0.25 mmol to prepare the NiTi-LDH-0.25SDS precursor. The other steps are basically the same as in Example 1 to prepare the MgH2-6%NiO-TiO2-0.25SDS composite hydrogen storage material.
[0127] Example 6
[0128] (1) Preparation of NiTi-LDH-0.75SDS precursor
[0129] This step is basically the same as in Example 1, except that the doping amount of sodium dodecyl sulfate (SDS) is changed to 0.75 mmol to obtain the NiTi-LDH-0.75SDS precursor.
[0130] The other steps are basically the same as in Example 1, and MgH2-6%NiO-TiO2-0.75SDS composite hydrogen storage material is obtained.
[0131] Example 7
[0132] (1) Preparation of NiTi-LDH-1SDS precursor
[0133] This step is basically the same as in Example 1, except that the doping amount of sodium dodecyl sulfate (SDS) is changed to 1 mmol to obtain the NiTi-LDH-1SDS precursor.
[0134] The other steps are the same as in Example 1, and the MgH2-6%NiO / TiO2-1SDS composite hydrogen storage material is obtained.
[0135] Example 8
[0136] (1) Preparation of NiTi-LDH-0.25SDS precursor
[0137] This step is basically the same as in Example 2, except that the doping amount of sodium dodecyl sulfate (SDS) is changed to 0.25 mmol to obtain the NiTi-LDH-0.25SDS precursor.
[0138] The other steps are basically the same as in Example 2, and the MgH2-6%Ni-TiO2-0.25SDS composite hydrogen storage material is obtained.
[0139] Example 9
[0140] (1) Preparation of NiTi-LDH-0.75SDS precursor
[0141] This step is basically the same as in Example 2, except that the doping amount of sodium dodecyl sulfate (SDS) is changed to 0.75 mmol to obtain the NiTi-LDH-0.75SDS precursor.
[0142] The other steps are basically the same as in Example 2, and MgH2-6%Ni-TiO2-0.75SDS composite hydrogen storage material is obtained.
[0143] Example 10
[0144] (1) Preparation of NiTi-LDH-1SDS precursor
[0145] This step is basically the same as in Example 2, except that the doping amount of sodium dodecyl sulfate (SDS) is changed to 1 mmol to obtain the NiTi-LDH-1SDS precursor.
[0146] (2) Other steps are basically the same as in Example 2, and MgH2-6%Ni-TiO2-1SDS composite hydrogen storage material is obtained.
[0147] The three catalysts prepared in Examples 8 to 10 were subjected to structural testing. The results showed that, based on the characterization results of the three catalysts Ni / TiO2-0.025SDS, Ni / TiO2-0.075SDS, and Ni / TiO2-0.1SDS, the microstructure of Ni / TiO2-0.025SDS and Ni / TiO2-0.075SDS failed to maintain the nanosheet structure, which was inconsistent with the experimental assumption. Due to the excessive SDS doping, the precursor NiTi-LDH-0.1SDS did not show the characteristic diffraction peaks of the hydrotalcite-like structure.
[0148] Example 11
[0149] The process is basically the same as in Example 1, except that the calcination temperature in step (2) is different. The calcination temperature of the calcination treatment is changed to 400℃ to obtain the NiO-TiO2-0.5SDS-400 catalyst.
[0150] The other steps are basically the same as in Example 1.
[0151] Example 12
[0152] The process is basically the same as in Example 1, except that the calcination temperature in step (2) is different. The calcination temperature of the calcination treatment is changed to 500℃ to obtain the NiO-TiO2-0.5SDS-500 catalyst.
[0153] The other steps are basically the same as in Example 1.
[0154] Example 13
[0155] The process is basically the same as in Example 1, except that the calcination temperature in step (2) is different. The calcination temperature of the calcination treatment is changed to 550°C to obtain the NiO-TiO2-0.5SDS-550 catalyst.
[0156] The other steps are basically the same as in Example 1.
[0157] Example 14
[0158] The process is basically the same as in Example 2, except that the calcination temperature in step (2) is different. The calcination temperature of the calcination treatment is changed to 400℃ to obtain the Ni-TiO2-0.05SDS-400 catalyst.
[0159] The other steps are basically the same as in Example 2.
[0160] Example 15
[0161] The process is basically the same as in Example 2, except that the calcination temperature in step (2) is different: the calcination temperature of the calcination treatment is changed to 500℃ to obtain Ni-TiO2-0.05SDS-500 catalyst.
[0162] The other steps are basically the same as in Example 2.
[0163] Comparative Example 1
[0164] Comparative Example 1, compared to Example 1, did not include a catalyst.
[0165] 1g of commercial MgH2 was ball-milled for 20h under a high-purity argon atmosphere to obtain ball-milled MgH2 powder. The ball-to-material ratio was 20:1, the rotation speed was 400rpm, the ball mill jar was a 100mL stainless steel jar, and the grinding balls were stainless steel grinding balls with diameters of 5mm and 10mm. The ball milling method was used in both forward and reverse intermittent ball milling to prepare pure ball-milled MgH2 powder.
[0166] Test case
[0167] The materials prepared above were subjected to structural tests using conventional testing methods well-known in the art. The test results are as follows:
[0168] Figure 1 The XRD patterns of the NiTi-LDH-0.5SDS precursor prepared in step (1) of Example 1 and the NiTi-LDH prepared in step (1) of Example 3 are shown. Figure 1As shown, the crystal plane diffraction peaks of NiTi-LDH-0.5SDS in Example 1 are consistent with the characteristic diffraction peaks of the hydrotalcite-like structure, proving the successful synthesis of the precursor. Furthermore, the (003) peak of the NiTi-LDH-0.5SDS precursor in Example 1 is shifted to the left compared to the (003) peak of the undoped NiTi-LDH in Example 3, indicating that the interlayer spacing of the two-dimensional layered material with added surfactant SDS is further expanded.
[0169] Figure 2 The image shows the XRD pattern of the NiO-TiO2-0.5SDS composite catalyst prepared in step (2) of Example 1. Figure 2 It can be seen that after calcination, the characteristic peaks of the nickel-titanium hydrotalcite precursor have disappeared, and the Ni in NiTi-LDH-0.5SDS has also disappeared. 2+ Transformation into NiO, Ti 4+ When converted to TiO2, the characteristic diffraction peaks corresponding to NiO and TiO2 can be clearly observed in the figure, indicating that the composite catalyst is mainly composed of NiO phase and TiO2.
[0170] Figure 3 This is a SEM image of the NiO-TiO2-0.5SDS composite catalyst prepared in step (2) of Example 1. From... Figure 3 It can be seen that the NiO-TiO2-0.5SDS catalyst still maintains the nanosheet structure, and its morphology is a three-dimensional flower-like morphology formed by the self-assembly of ultrathin nanosheets, with each flower cluster having a size of about 3μm to 5μm.
[0171] Figure 4 The images show the SEM images and particle size distribution of the MgH2-6%NiO-TiO2-0.5SDS composite hydrogen storage material prepared in Example 1. Figure 4 It can be seen that after mechanical ball milling, the average particle size of the composite hydrogen storage material is 0.59 μm.
[0172] Figure 5 The image shows the XRD pattern of the Ni-TiO2-0.5SDS catalyst prepared in Example 2. Figure 5 The results show that after calcination and reduction of NiTi-LDH-0.5SDS, the characteristic peaks of the nickel-titanium hydrotalcite precursor have disappeared, and the Ni in NiTi-LDH-0.5SDS... 2+ Reduced to Ni, Ti 4+ It is converted into TiO2. From Figure 5 The characteristic diffraction peaks corresponding to metallic Ni and TiO2 can also be clearly observed, indicating that the composite catalyst was successfully synthesized.
[0173] Figure 6This is a SEM image of the Ni-TiO2-0.5SDS composite catalyst prepared in Example 2. From... Figure 6 It can be seen that the Ni-TiO2-0.5SDS catalyst still maintains the nanosheet structure. The catalyst retains the nanosheet assembly characteristics of the precursor at the mesoscale. These nanosheets are intertwined and tightly connected, eventually forming a three-dimensional network structure with abundant pores.
[0174] Figure 7 The images show the SEM images and particle size distribution of the MgH2-6%Ni-TiO2-0.5SDS composite hydrogen storage material prepared in Example 2. Figure 7 It can be seen that after mechanical ball milling, the average particle size of the composite hydrogen storage material is 0.78 μm.
[0175] Figure 8 The XRD patterns and SEM images of the NiTi-LDH-0.5SDS precursor prepared in Example 1 are compared with those of the NiTi-LDH-xSDS precursors (x = 0.25, 0.75, 1) prepared in Examples 5-7. According to the test results, the NiTi-LDH-0.25SDS sample in Example 5 exhibits a layered stacking phenomenon, while the NiTi-LDH-0.75SDS sample in Example 6 and the NiTi-LDH-1SDS sample in Example 7 show severe nanoparticle aggregation. The microstructure of NiTi-LDH-0.25SDS and NiTi-LDH-0.75SDS failed to maintain a nanosheet-like structure. Due to excessive SDS doping, the NiTi-LDH-1SDS precursor did not show the characteristic diffraction peaks of a hydrotalcite-like structure. The NiTi-LDH-0.5SDS sample in Example 1 exhibits an interwoven nanosheet structure with no agglomeration on the sheet surface, which may give it a larger specific surface area and provide more catalytic active sites. Based on its structural integrity and morphological advantages, NiTi-LDH-0.5SDS is the preferred precursor material.
[0176] Figure 9The XRD patterns and SEM images of the NiO-TiO2-0.5SDS catalyst prepared in Example 1 and the NiO-TiO2-0.5SDS-T (T=400, 500, 550) catalysts prepared in Examples 11 to 13 at different calcination temperatures are compared. The results show that the product after calcining the NiTi-LDH-0.5SDS precursor at 400℃ did not exhibit obvious TiO2 diffraction peaks, indicating that the titanium oxide has low crystallinity or exists in an amorphous form. After calcination at 500℃ and 550℃, the lamellar structure of the product showed some collapse, and the lamellars also curled. Based on the structural characterization data, calcining the precursor at 450℃ can achieve complete crystallization of NiO and TiO2, effectively control grain size, and retain the morphological characteristics of the precursor. These structural characteristics are beneficial for exposing more active sites.
[0177] Hydrogen storage performance test
[0178] The hydrogen storage performance of the composite hydrogen storage materials prepared in Examples 1 and 2 was tested using the following methods: 60 mg of the composite hydrogen storage material was weighed in a glove box, and the hydrogen desorption curve of the sample with temperature was tested using a PCTpro high-pressure gas adsorption instrument; the isothermal hydrogen desorption curves at 300℃ and 250℃ with an initial hydrogen pressure of 0.01 MPa; the isothermal hydrogen adsorption curves at 75℃ and 150℃ with an initial hydrogen pressure of 3 MPa; and the hydrogen adsorption and desorption curves after 50 cycles at 300℃.
[0179] The hydrogen storage performance of the composite hydrogen storage materials prepared in Examples 3 and 4 was tested. The test method is as follows: 60 mg of composite hydrogen storage material powder was weighed in a glove box, and the hydrogen desorption curve of the sample with temperature was tested using a PCTpro high-pressure gas adsorption instrument; as well as the isothermal hydrogen desorption curves at 300℃ and 250℃ with an initial hydrogen pressure of 0.01 MPa.
[0180] The hydrogen storage performance of the hydrogen storage material of Comparative Example 1 was tested using the following methods: 60 mg of ball-milled pure MgH2 powder prepared in Comparative Example 1 was weighed in a glove box, and the hydrogen desorption curve of the sample with temperature was tested using a PCTpro high-pressure gas adsorption instrument; the isothermal hydrogen desorption curve at 300℃ and 0.01 MPa initial hydrogen pressure; and the isothermal hydrogen adsorption curve at 150℃ and 3 MPa initial hydrogen pressure.
[0181] The test results are as follows:
[0182] Figure 10 The temperature-dependent hydrogen desorption (TPD) curves of the ball-milled pure MgH2 powder of Comparative Example 1, the MgH2-6 NiO / TiO2-0.5SDS prepared in Example 1, and the MgH2-6 Ni / TiO2-0.5SDS composite hydrogen storage materials prepared in Example 2 are shown below. Figure 10 It can be seen that the initial hydrogen release temperature of the MgH2-6 NiO / TiO2-0.5SDS composite hydrogen storage material prepared in Example 1 is 215.8℃, which is much lower than the initial hydrogen release temperature of ball-milled pure MgH2 in Comparative Example 1 (290.1℃); the initial hydrogen release temperature of the MgH2-6 Ni / TiO2-0.5SDS composite hydrogen storage material prepared in Example 2 is 209.8℃, which is much lower than the initial hydrogen release temperature of ball-milled pure MgH2 (290.1℃).
[0183] Figure 11 The isothermal hydrogen desorption curves are shown for ball-milled pure MgH2 powder (Comparative Example 1) and the MgH2-6 NiO / TiO2-0.5SDS composite hydrogen storage material prepared in Example 1. From... Figure 11 It can be seen that the hydrogen release capacity and rate of the MgH2-6NiO-TiO2-0.5SDS composite hydrogen storage material prepared in Example 1 are significantly improved. It exhibits a large hydrogen release capacity (6.48 wt.%) at 300℃, while ball-milled pure MgH2 can only release 0.03 wt.% hydrogen in 5 minutes at the same temperature, almost none. Even with the hydrogen release time extended to 60 minutes, ball-milled pure MgH2 can only release 3.68 wt.% hydrogen. Even at temperatures as low as 250℃, this composite material can rapidly release 6.05 wt.% hydrogen within 15 minutes.
[0184] Figure 12 Isothermal hydrogen absorption curves are shown for ball-milled pure MgH2 powder (Comparative Example 1) and the MgH2-6%NiO-TiO2-0.5SDS composite hydrogen storage material prepared in Example 1. From... Figure 12 It can be seen that the MgH2-6%NiO-TiO2-0.5SDS composite hydrogen storage material prepared in Example 1 also possesses excellent low-temperature hydrogen absorption performance. After adding the catalyst, the composite hydrogen storage material can rapidly absorb 5.42 wt.% hydrogen within 10 minutes at 150°C, while ball-milled pure MgH2 can only absorb 1.35 wt.% hydrogen within 10 minutes at the same temperature. Even with the absorption time extended to 60 minutes, ball-milled pure MgH2 can only absorb 2.94 wt.% hydrogen. Even at a lower temperature of 75°C, this composite material can absorb 2.98 wt.% hydrogen within 30 minutes.
[0185] Figure 13 The graph shows the hydrogen absorption and desorption performance at 300℃ of the MgH2-6%NiO-TiO2-0.5SDS composite hydrogen storage material prepared in Example 1. (From...) Figure 13It can be seen that after 50 cycles of hydrogen absorption and desorption, the hydrogen storage capacity of the MgH2-6%NiO-TiO2-0.5SDS composite hydrogen storage material remained at 6.12 wt.%, with a capacity retention rate of 95.03%, demonstrating stable cycle reversibility.
[0186] Figure 14 The isothermal hydrogen desorption curves are shown for ball-milled pure MgH2 powder (Comparative Example 1) and the MgH2-6%Ni-TiO2-0.5SDS composite hydrogen storage material prepared in Example 2. From... Figure 14 It can be seen that the hydrogen release capacity and rate of the MgH2-6%Ni-TiO2-0.5SDS composite hydrogen storage material prepared in Example 2 are significantly improved. It exhibits a large hydrogen release capacity (6.41 wt.%) at 300℃, while ball-milled pure MgH2 can only release 0.03 wt.% hydrogen in 5 minutes at the same temperature, almost none. Even with the hydrogen release time extended to 60 minutes, ball-milled pure MgH2 can only release 3.68 wt.% hydrogen. Even at temperatures as low as 250℃, this composite material can rapidly release 5.85 wt.% hydrogen within 15 minutes.
[0187] Figure 15 Isothermal hydrogen absorption curves are shown for ball-milled pure MgH2 powder (Comparative Example 1) and the MgH2-6%Ni-TiO2-0.5SDS composite hydrogen storage material prepared in Example 2. From... Figure 15 It can be seen that the MgH2-6%Ni-Ti O2-0.5SDS composite hydrogen storage material prepared in Example 2 also has excellent low-temperature hydrogen absorption performance. After adding the catalyst, the composite hydrogen storage material can rapidly absorb 5.31 wt.% hydrogen at 150℃ within 10 min, while ball-milled pure MgH2 can only absorb 1.35 wt.% hydrogen at the same temperature within 10 min. When the hydrogen absorption time is extended to 60 min, ball-milled pure MgH2 can only absorb 2.94 wt.% hydrogen. Even at a lower temperature of 75℃, the composite material can absorb 3.44 wt.% hydrogen within 30 min.
[0188] Figure 16 The graph shows the hydrogen absorption and desorption performance at 300℃ of the MgH2-6%Ni-TiO2-0.5SDS composite hydrogen storage material prepared in Example 2. (From...) Figure 16 It can be seen that after 50 cycles of hydrogen absorption and desorption, the hydrogen storage capacity of the MgH2-6%Ni-TiO2-0.5SDS composite hydrogen storage material remains at 6.23 wt.%, with a capacity retention rate of 95.55%, demonstrating excellent cycle reversibility.
[0189] Figure 17The hydrogen desorption (TPD) curves of the MgH2-6%NiO-TiO2 composite hydrogen storage materials prepared in Example 3 and Example 4 are shown. Figure 17 It can be seen that the initial hydrogen release temperature of the MgH2-6%NiO-TiO2 composite hydrogen storage material is reduced to 226.6℃, and the initial hydrogen release temperature of the MgH2-6%Ni-TiO2 composite hydrogen storage material is reduced to 222.1℃.
[0190] Figure 18 The isothermal hydrogen desorption test results of the MgH2-6%NiO-TiO2 composite hydrogen storage material in Example 3 are as follows: Figure 18 It can be seen that, under the conditions of a target hydrogen release temperature of 300℃ and a hydrogen release time of 5 min, the hydrogen release amount of MgH2-6%NiO-TiO2 is 5.75 wt.%; under the conditions of a hydrogen release temperature of 250℃ and a hydrogen release time of 15 min, its hydrogen release amount is 2.14 wt.%. Figure 19 The isothermal hydrogen desorption test results of the MgH2-6%Ni-TiO2 composite hydrogen storage material in Example 4 are as follows: Figure 19 It can be seen that, under the conditions of a target hydrogen release temperature of 300℃ and a hydrogen release time of 5 min, the hydrogen release amount of MgH2-6%Ni-TiO2 is 5.73 wt.%; under the conditions of a hydrogen release temperature of 250℃ and a hydrogen release time of 15 min, its hydrogen release amount is 2.49 wt.%.
[0191] Compared with ball-milled pure MgH2 powder, the hydrogen release capacity and rate of MgH2-6%NiO-TiO2 in Example 3 were improved. However, at the same temperature, the isothermal hydrogen release performance of MgH2-6%NiO-TiO2 was not as good as that of MgH2-6%NiO-TiO2-0.5SDS (e.g., ...). Figure 11 Especially at lower temperatures, such as 250℃, MgH2-6%NiO-TiO2-0.5SDS can achieve complete hydrogen release within 15 minutes, with a hydrogen release amount as high as 6.05 wt.%, while MgH2-6%NiO-TiO2 only releases 2.14 wt.% of hydrogen in the same time. This indicates that the doping of the surfactant SDS can ensure that the precursor morphology is maintained after calcination, resulting in a more dispersed catalyst morphology, reduced particle agglomeration, and finer particle size, which helps to improve the catalytic effect.
[0192] In summary, the LDH derivatives prepared using LDH as a nanosheet structure carrier and as a precursor through certain post-processing methods have the following characteristics: they maintain the ultrathin / hollow structure of the precursor while fully utilizing the advantages of the multi-metal composition of the LDH precursor to form related metal element doping or heterojunctions, thereby optimizing the material's composition and structure. Therefore, the materials prepared using LDH as a precursor possess abundant reactive sites and can achieve enhanced intrinsic properties through doping / heterojunction formation. Furthermore, NiTi-LMO catalysts can be synthesized in a one-step process; this catalyst preparation method is simple, the raw materials are readily available, and it is suitable for large-scale production.
[0193] Furthermore, this invention further designs layered NiTi-LMO-SDS (NiO / TiO2-SDS and Ni / TiO2-SDS) catalysts derived from NiTi-LDH-surfactant SDS precursors. Specifically, a simple one-step co-precipitation method is used to prepare an SDS-doped NiTi-LDH precursor (NiTi-LDH-SDS) with an upright, interlaced sheet-like structure. Subsequently, a highly dispersed nano-metal catalyst (NiTi-LMO-SDS) is obtained through a suitable calcination process. This catalyst is then used for the hydrogen absorption and desorption catalysis of MgH2. The hydrogen storage catalyst is mechanically ball-milled with magnesium hydride to obtain a composite hydrogen storage material. After being combined with magnesium hydride, the catalyst exhibits excellent catalytic effects, specifically in the following aspects: (1) it increases the hydrogen absorption rate and the amount of hydrogen absorbed; (2) it increases the amount of hydrogen released and the rate of hydrogen release; (3) it has stable hydrogen storage cycle kinetics, and the hydrogen storage capacity can still be maintained at over 95% after 50 hydrogen absorption and desorption cycles.
[0194] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A modified magnesium hydride composite material for hydrogen storage materials, characterized in that, The composite material includes a NiTi-LMO composite catalyst and MgH2, wherein LMO represents a layered metal oxide; The NiTi-LMO composite catalyst is prepared by the following method: mixing a nickel source, a titanium source, and a precipitant, and preparing a NiTi-LDH precursor by heating the reaction; a surfactant is also added in the step of preparing the NiTi-LDH precursor. The NiTi-LDH precursor was calcined in an argon atmosphere at a temperature of 450℃. In the NiTi-LMO composite catalyst, the molar ratio of Ni to Ti is (3-4):1; the molar ratio of the surfactant to Ti is less than 1:
1. The surfactant includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium fatty alcohol ether sulfate.
2. The composite material according to claim 1, characterized in that, The molar ratio of the surfactant to the Ti is (0.25–0.75):
1.
3. The composite material according to any one of claims 1 to 2, characterized in that, The composite material comprises, by mass percentage, 3 wt.% to 9 wt.% of the NiTi-LMO composite catalyst and 91 wt.% to 97 wt.% of the MgH2.
4. The composite material according to any one of claims 1 to 2, characterized in that, The NiTi-LMO composite catalyst is a NiO-TiO2 layered metal oxide and / or a Ni-TiO2 layered metal oxide.
5. A method for preparing a modified magnesium hydride composite material as described in any one of claims 1 to 4, characterized in that, Includes the following steps: A nickel source, a titanium source, and a precipitant were mixed and a NiTi-LDH precursor was prepared by heating the mixture. A surfactant was also added during the preparation of the NiTi-LDH precursor. The NiTi-LDH precursor was calcined under a protective atmosphere to prepare a NiTi-LMO composite catalyst; the calcination temperature was 450℃. The NiTi-LMO composite catalyst was mixed with MgH2 to prepare the composite material.
6. The preparation method according to claim 5, characterized in that, One or more of the following conditions must be met: (1) The molar ratio of the surfactant to the titanium source is less than 1:1; (2) The surfactant includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and sodium fatty alcohol ether sulfate.
7. The preparation method according to any one of claims 5 to 6, characterized in that, One or more of the following conditions must be met: (1) The molar ratio of the nickel source to the titanium source is (3-4):1; (2) The molar ratio of the titanium source to the precipitant is 1:(50~100). (3) The nickel source includes one or more of nickel chloride, nickel nitrate and nickel carbonate; (4) The titanium source includes one or more of isopropyl titanate, tetrabutyl titanate, titanium tetrachloride and titanium tetraisopropoxide; (5) The precipitant includes urea.
8. A hydrogen storage material, characterized in that, The hydrogen storage material includes the modified magnesium hydride composite material according to any one of claims 1 to 4 or the modified magnesium hydride composite material prepared by the preparation method according to any one of claims 5 to 7.
